Endoscopic-assisted craniosynostosis surgery: First case series in India - Derick A Mendonca; Venkat Ramamurthy; Swaroop Gopal; Rajendra S Gujjalanavar (Wolters Kluwer Medknow Publications, 2019)
Introduction: Craniosynostosis is a congenital pathological condition resulting from premature fusion of sutures of the cranial vault and leads to an abnormal head shape with a significant risk of raised intracranial pressure. Surgical correction techniques have seen a constant evolution from an extensive open procedure to the relatively new minimally invasive craniosynostosis technique. The current center introduced this new procedure in India since 2015. Aims and Objectives: This article documents our experience as the first team in the country to correct craniosynostosis endoscopically with emphasis on planning, surgical techniques, and helmet therapy to achieve the optimum result. Materials and Methods: This is a prospective case series of six patients with anterior craniosynostosis corrected endoscopically and followed up with postoperative custom-made cranial helmet. All patients were nonsyndromic with no associated anomalies. The mean age of surgical intervention was 92.6 days (84-100 days), mean duration of surgery was 61.7 min (54-74 min), mean blood loss was 55 ml (50 ml-60 ml), and mean duration of hospital stay was 2 days (2-3 days). No complications and mortality were reported. Conclusion: This case series has demonstrated that endoscopically assisted craniosynostosis correction is a safe, effective, and reliable technique in the armamentarium of a craniofacial surgeon. The minimally invasive nature allows early intervention in children. Parental compliance is important in helmet therapy which forms an integral part of this surgery for correction of the abnormal head shape. We believe that every patient with nonsyndromic single-suture craniosynostosis should be offered endoscopic correction before the age of 6 months.